Excessively High Maternal Total Cell-Free DNA Concentration and Fetal Growth Restriction in Singleton Pregnancies: A Retrospective Cohort Study - Lingling Xing; Xiaosha Jing; Ting Bai; Sha Liu; Jianlong Liu; Cechuan Deng; Tianyu Xia; Yunyun Liu; Xiang Wei; Yuan Luo; Quanfang Zhou; Qian Zhu; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Noninvasive prenatal screening (NIPS) fails in approximately 0.2% of cases due to high maternal plasma total cell-free DNA (t-cfDNA) concentration (≥0.6 ng/µL) confirmed after two DNA extraction attempts. The clinical implications of this quality control metric for fetal growth restriction (FGR) remain unknown. Methods: This retrospective cohort study, conducted in a major prenatal diagnosis center in China, involved pregnant women who underwent noninvasive prenatal screening (NIPS) between 2019 and 2024. From a total of 73,636 pregnancies, 102 singleton pregnancies with excessively high t-cfDNA concentration (≥0.6 ng/µL upon retesting) leading to NIPS failure were compared with 396 matched controls (t-cfDNA < 0.6 ng/µL) after propensity score matching. The primary outcome was FGR, defined as estimated fetal weight or abdominal circumference below the 10th percentile for gestational age. Results: In the matched cohort, FGR occurred in 26.47% of the high-concentration group versus 9.60% of controls (OR = 3.27, 95% CI: 1.45–7.41, p = 0.004). The high-concentration group also had lower gestational age at delivery (37.44 vs. 38.48 weeks, p < 0.001) and higher preterm birth rates (18.63% vs. 7.57%, p = 0.025). Subgroup analyses for severe and FGR first detected before 32 weeks were exploratory and limited by statistical power, warranting cautious interpretation. Conclusions: An excessively high maternal t-cfDNA concentration in early pregnancy shows a significant association with FGR and adverse pregnancy outcomes. These findings suggest that t-cfDNA could potentially serve as an early biomarker for identifying pregnancies at elevated risk of FGR. Further validation of our findings in prospective studies is required to establish its clinical utility.